Kajian Optimalisasi Lahan Pertanian Pada Daerah Irigasi Sungai Paku Kecamatan Kampar Kiri Kabupaten Kampar - Karnanda, Eka Jevri; Mudjiatko, Mudjiatko; Siswanto, Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Changing at land used in Sei Paku Irrigation area caused the change of potential land from Â± 1132 hectares to Â± 373 hectares . This resulted in the failure of the rice granary program by the Riau provincial government., Resulting in declining agricultural productivity and incomeof the farmer community. Simulations done using linear programming optimization model with the help of SolverLinear Programming to get the value of the biggest advantages of multiple cropping patterns are applied.Thecropping pattern which gave benefit for the optimization is the 8th alternative ( Palawija/Fishpond -Palawija/Fishpond - Palawija/Fishpond). Replenishing water started at2ndperiod of December, in the area for crop season I: 0 hectares for Palawija and 493.09 hectares for Fishpond. Crop season II:0 hectares for Palawija and 314.74 hectares for Fishpond. Crop season III:0 hectares for Palawija and 542.90 hectares for Fishpond with benefit every year wasRp 25,659,599,866.55. However, the cropping pattern was not in accordance with thecropping patternplanned for agriculture. Therefore, the researcher chose the 1st whizh was Rice - Rice - Rice The pattern with planting started at 2nd period of February, inthe area for 1stplanting season was 457.41 hectares, 2ndplanting season was 325.05 hectares, 3rd planting season was 680, 01 Ha. The total of benefit gained every year was IDR 22,814,536,868.18.Keywords: Cropping pattern, optimize, linear Program